The effect of brushing with Salvadora persica (miswak) sticks on salivary Streptococcus mutans and plaque levels in children: a clinical trial - Heba J. Sabbagh; Khalil S. AlGhamdi; Hattan T. Mujalled; Sara M. Bagher (BMC, 2020)
Abstract Background The aim of the randomized double-blinded clinical trial was to evaluate the effect of tooth brushing with Salvadora persica (miswak) sticks on Streptococcus mutans count and the mean plaque score relative to brushing with fluoridated tooth paste (FTP). Methods Our sample included 94 healthy, high caries-risk, 8 to 9-year-old students recruited from a government school, in Jeddah, Saudi Arabia between February and April 2016. Subjects were randomly grouped into test (provided with miswak sticks) and control groups (provided with FTP and soft brushes). Both groups were introduced to a preparatory period (PPP) of 3 weeks. Plaque score and saliva sampling were conducted prior to the PPP and in follow-up visits by a single, calibrated and blinded dentist. Results Both groups showed a statistically significant decrease in the mean plaque score across the study (P = 0.007 and P = 0.001, respectively). In addition, subjects in the test group with abundant S. sanguinis increased from zero to six after 3 months. Conclusions Salvadora Persica (miswak) and brushing with FTP significantly reduced plaque scores among school children. In addition, Salvadora persica was found to change the proportions of salivary bacteria in favor of species with less risk of inducing caries. Trial registration ClinicalTrials.gov ID #: NCT04137393.